2011
DOI: 10.1086/659761
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ATP Bioluminescence Assays for Potential Use in a Hospital Setting

Abstract: ATP bioluminescence is being applied in hospitals to measure surface contamination. We compared commercial luminometers for detecting the number Staphylococcus aureus associated with surfaces. The data showed that the ATP bioluminescence methods tested were not robust enough to generate quantitative data on bacterial numbers, especially at low concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 8 publications
4
33
0
Order By: Relevance
“…The benchmark levels range from 25 to 500 relative light units (RLU) for 10-to 100-cm 2 health care surfaces (238,241,247). Studies have suggested that some systems are not sufficiently sensitive to detect very low microbial counts (Ͻ10 CFU/cm 2 ), which is of concern given the low numbers of pathogens required to initiate infection (Table 1) (248,249). Other studies have investigated possible associations between ATP and microbiological data by systematically measuring both data sets from the same surfaces.…”
Section: Atp Bioluminescence Systemsmentioning
confidence: 99%
“…The benchmark levels range from 25 to 500 relative light units (RLU) for 10-to 100-cm 2 health care surfaces (238,241,247). Studies have suggested that some systems are not sufficiently sensitive to detect very low microbial counts (Ͻ10 CFU/cm 2 ), which is of concern given the low numbers of pathogens required to initiate infection (Table 1) (248,249). Other studies have investigated possible associations between ATP and microbiological data by systematically measuring both data sets from the same surfaces.…”
Section: Atp Bioluminescence Systemsmentioning
confidence: 99%
“…Thus, the relation between RLU and colony-forming units is not linear. [22][23] The comparison of the three friction techniques adopted in this research, using ATP detection as an evaluation parameter, aimed to establish which of the techniques would be capable of removing dirtiness from surfaces in order to measure and reproduce it. We found that the cleaning/disinfection was efficient with no statistically significant difference among the friction techniques in terms of organic material reduction on surfaces that are commonly found in clinical environments.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, the luciferase enzyme catalyses the transformation of luciferin to oxyluciferin where transition to the basic state due to the emission of light with an intensity proportional to the amount of ATP in the sample [2,11,12]. The intensity of light impulses that are formed in the luminescence reaction is measured at 562 nm and is expressed in Relative Light Units (RLU).…”
Section: Oxyluciferin + Amp + Products + Lightmentioning
confidence: 99%
“…It can be also applied in facilities for relaxation and recreation, such as swimming pools and water parks. It must be remembered that the referential values should be properly selected for the chosen utility surface and its usage [11,[22][23][24]. Griffith et al [25] established a procedure for analysing the microbiological pollution of surfaces (Fig.…”
Section: Using Atp Tests In Practicementioning
confidence: 99%